Dietary fish oil and DHA down-regulate antigen-activated CD4+ T-cells while promoting the formation of liquid-ordered mesodomains. Issue 2 (28th January 2014) - Kim, Wooki; Barhoumi, Rola; McMurray, David N.; Chapkin, Robert S.
<x content-type="archive" xml:space="preserve">Abstract</x> We have demonstrated previously that n-3 PUFA endogenously produced by fat-1 transgenic mice regulate CD4+ T-cell function by affecting the formation of lipid rafts, liquid-ordered mesodomains in the plasma membrane. In the present study, we tested the effects of dietary sources of n-3 PUFA, i.e. fish oil (FO) or purified DHA, when compared with an n-6 PUFA-enriched maize oil control diet in DO11.10 T-cell receptor transgenic mice. Dietary n-3 PUFA were enriched in CD4+ T-cells, resulting in the increase of the n-3:n-6 ratio. Following antigen-specific CD4+ T-cell activation by B-lymphoma cells pulsed with the ovalbumin 323–339 peptide, the formation of liquid-ordered mesodomains at the immunological synapse relative to the whole CD4+ T-cell, as assessed by Laurdan labelling, was increased (P< 0·05) in the FO-fed group. The FO diet also suppressed (P< 0·05) the co-localisation of PKCθ with ganglioside GM1 (monosialotetrahexosylganglioside), a marker for lipid rafts, which is consistent with previous observations. In contrast, the DHA diet down-regulated (P< 0·05) PKCθ signalling by moderately affecting the membrane liquid order at the immunological synapse, suggesting the potential contribution of the other major n-3 PUFA components of FO, including EPA.